PENGARUH PERPUTARAN KREDIT, KECUKUPAN MODAL, DAN JUMLAH NASABAH PADA PROFITABILITAS LEMBAGA PERKREDITAN DESA (LPD) DI KABUPATEN BADUNG PERIODE 2010-2012 - pudja, Ayu Dwikayanthi (E-Jurnal Akuntansi, 2014)
ABSTRACT Development of Village Credit Institutions (LPD) to support economic development, one of which is the LPD Badung regency. This study was purpose of  the determine turnover of credit, capital adequacy, and the number of customers LPD affect the ability to generate earnings. Sampling method using purposive sampling, and obtained 342 LPD. Hypothesis testing using multiple regression techniques. Partial test shows that capital adequacy, credit turnover, and the number of customers affect the profitability of LPD in Badung regency period 2010-2012.
Keywords: Kredit, Modal, Nasabah, Return On Equity, Profitabilitas